THE INFLUENCE OF EXPORT AND INVESTMENTS ON INSTRUMENTS OF RESERVES IN INDONESIA 2006-2015 - Sakinah; Talbani Farlian (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2020)
This study aims to examine the relationship between exports and foreign investment in foreign exchange reserves. This study uses causality design with quantitative methods. The data used in this study are secondary data in the form of time series for the period 2006-2015. This study uses multiple linear regression analysis methods. Based on the simultaneous F test results of exports and foreign investment there is a significant positive effect on inflation. the results of the t test show that exports partially have a significant positive effect on foreign exchange reserves. While foreign investment does not affect foreign exchange reserves.